Enhancement Effectiveness Learning Through Strategy Learning Whichinteractive and Creative - Sabrina Putri (International Journal of Students Education, 2024)
Learning strategies are steps that support students' ease in the process study. Strategy identical with technique, strategy or tips, However if combined with say learning(learning strategy) can be understood as a method or set of methods or techniques that carried out by a teacher or student in trying to bring about a change behavior or attitude. This process includes selecting methods, media, sequence of material, and scope of material in accordance, for achieve competency learning. strategy choice which right no only facilitate the achievement of learning objectives, but also increase the effectiveness of learning overall. The importance of choosing a strategy by considering certain criteria, such as objective study, characteristics learners, and factor other, so that process learning can optimal. This research aims to explore effective learning strategies to increase vocational school students' self-confidence in learning mathematics. The research results show that implementing student-oriented learning strategies, such as group discussions and providing constructive feedback, can significantly increase students' self-confidence in studying mathematics. Learning strategies that pay attention to student needs and provide appropriate support can have a positive impact on increasing student self-confidence.